Corrosion Inhibition of Carbon Steel in Hydrochloric Acid under Dynamic Conditions - Slaiman, Q.J.M.; Eirs, Jaafar C. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
In this work, studying the effect of ethylenediamine as a corrosion inhibitor was investigated for carbon steel in aerated HCl solution in range of 0.1-1N under dynamic conditions, i.e., rotational velocity of 400–1200 rpm in the temperature range 35 – 65 ºC. Weight loss method was employed in absence and presence of the inhibitor as an adsorption type in concentration range 1000 – 5000 ppm using rotating cylinder specimens. The experimental results showed that corrosion rate in absence and presence of inhibitor is increased with increasing temperature, rotational velocity and concentration of acid. It is decreased with increasing inhibitor concentration for the whole range of temperature, rotational velocity and concentration of acid solution. Under these conditions maximum inhibition efficiency obtained was 86% while minimum inhibition efficiency was 36%. The adsorption of this inhibitor on carbon steel surface is found to obey Langmuir adsorption isotherm.